A Qualitative Study Exploring the Usability of Nintendo Wii Fit among Persons with Multiple Sclerosis. (24th April 2013) - Plow, Matthew; Finlayson, Marcia; Stein, Franklin; Hwang, Eric
Abstract The purpose of this study was to examine the usability of Nintendo Wii Fit to promote physical activity in adults with multiple sclerosis. Qualitative interviews were conducted as part of a pilot study that examined the health outcomes of a 14‐week Wii Fit home‐exercise programme in 30 adults with multiple sclerosis. We found participants reported that Wii Fit helped build confidence in abilities, achieve goals related to engagement in leisure activities and remove barriers associated with going to a gym to exercise. However, Wii Fit induced initial reactions of intimidation and worries about falling, and feedback during game play reminded participants of their impairments. Wii Fit was limited in its customizability to accommodate different functional levels. Understanding how to improve the usability and customizability of commercially available exergaming technology could be of benefit to people with disabling conditions. Before conducting randomized controlled trials of commercially available exergaming technology in adults with disabling conditions, we recommend that strategies be identified to remove usability barriers so those with moderate impairments can be included in the trial. This will reduce the likelihood of ceiling effects and clinical irrelevance. In terms of clinical recommendations, rehabilitation professionals need to consider patients' functional level, surrounding environment and preferences when prescribing a Wii Fit‐based exercise programme. Copyright © 2013 John Wiley & Sons, Ltd.